Chronic cough management: dealing with a sensation of irritation in the throat. Issue 8 (28th October 2013) - Ogawa, Haruhiko; Fujimura, Masaki; Ohkura, Noriyuki; Makimura, Koichi
Abstract : Among the various types of laryngeal paraesthesia suffered by chronic cough patients, we often encounter 'a sensation of irritation in the throat (SIT)'. Our study indicated that capsaicin cough threshold was significantly ( P  < 0.05) lower in the SIT‐positive group (13.9 μmol/L) than in the SIT‐negative group (49.6 μmol/L). The establishment of treatment strategies for SIT would be advantageous for treating chronic cough patients suffering from this laryngeal sensation.